Precise Dimming and Color Control of LED Systems Based on Color Mixing - Lee,ATL; Chen,H; Tan,SC; Hui,SY (IEEE Transactions on Power Electronics, 2016)
This paper proposes a closed-loop nonlinear scheme for precisely controlling the luminosity and correlated color temperature (CCT) of a bicolor adjustable light-emitting diode (LED) lamp. The main objective is to achieve a precise and fully independent dimming and CCT control of the light mixture emitted from a two-string LED lamp comprising warm-white and cool-white color LEDs, regardless of the operating conditions and throughout the long operating lifetime of the LED lamp. The proposed control method is formulated using the nonlinear empirical LED model of the bicolor white LED system. Experimental results show that with the proposed closed-loop nonlinear approach, both CCT and dimming control of the bicolor lamp is significantly more accurate and robust to ambient temperature variations, ambient light interference, and LED aging than the conventional linear approach used in existing products. The maximum error in luminous flux employing the proposed closed-loop nonlinear approach is 3%, compared with 20% using the closed-loop linear approach. The maximum deviation in CCT is only 1.78%, compared with 27.5% with its linear counterpart.